MULTILINGUALISM IN THE CITY OF YAZD (IRAN) - E.K. Molchanova (Многоязычие в образовательном пространстве)
The article is devoted to the ancient city of Yazd in Iran and the multilingualism observed within this city. The city is the centre for Iranian Zoroastrians. All of them are bilingual: they speak their own language and the national Persian language. The article examines the changes which Zoroastrian Dari, the language of everyday communication of Zoroastrians, has already undergone and continues to experience under the influence of literary and colloquial Persian. Evidence is given of the reverse influence of Zoroastrian Dari on the Persian dialect of the city of Yazd, some observations are also made of the language of the Jews in the city of Yazd.